2019
DOI: 10.1111/jocd.13123
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related characterization of sensitive skin in normal young Chinese

Abstract: Background: While clinical signs, symptoms, as well as etiology of sensitive skin in general populations have been extensively studied over the last decades, characteristics of sensitive skin in normal subjects, particularly gender-related characteristics, still remain unknown.Objective: In the present study, we characterize facial sensitive skin in normal young Chinese. Subjects and Methods:A questionnaire was given to each participant aged 10-30 years. Clinical signs, symptoms, and associated trigger factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…One additional article was identified after reviewing references of relevant full texts . Finally, we included 26 articles representing general population in 18 countries ( n = 51 783) . The PRISMA flow diagram was presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One additional article was identified after reviewing references of relevant full texts . Finally, we included 26 articles representing general population in 18 countries ( n = 51 783) . The PRISMA flow diagram was presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive skin is an abnormal subclinical sensory response that includes tingling, tightness, burning or prickling, and possibly pain or itching that may be caused by medications, cosmetics, and toiletries, but without obvious symptoms [20]. In fact, people of different ages and genders have different levels of exposure to such irritants in different working or living environments, which may affect the development of sensitive skin symptoms [21]. A self‐scoring questionnaire was used in this study to subjectively assess sensitive skin conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Data on incidence from China differs from all other countries that have been surveyed. Three studies have been published on SSS in China: Farage and colleagues, and Xu and colleagues, and Wang and colleagues [7][8][9]. Among the surveyed populations these investigators found that only 23%, 40%, and 24%, respectively, responded they had any degree of skin sensitivity.…”
Section: A Global Phenomenon: Prevalence Of Sensitive Skin Around the Worldmentioning
confidence: 99%
“…Burning [9,21,22] Dryness [23] Itching [9,21,22] Pain [9,21,24] Prickling [21,22] Picking [21] Smarting [25] Stinging [24] Tickling [26] Tightening [9,22]…”
Section: Sensationmentioning
confidence: 99%